A regional-scale assessment of micro-organic contaminants in shallow groundwater in the Pearl River Delta, China. Issue 1 (3rd April 2021) - Wang, Jincui; Zhou, Bing; Cui, Haiwei; Liu, Chunyan; Zhang, Ying; Zhao, Yongsheng; Zhang, Yuxi; Sun, Jichao
Abstract: Industrialization and urban expansion can result in the contamination of shallow groundwater by micro-organics (MO) in the Pearl River Delta (PRD), China. This study provides a regional scale assessment of MO contaminants in shallow groundwater in the PRD, investigating the occurrence and distribution of different compound groups, highlighting the relationship between MOs and aquifers, and between MOs and land-use. The main influence of the vadose zone and regional socioeconomic development on each relationship is also analyzed. Twenty-one compounds were detected, with naphthalene, acetophenone, 2-methylnaphthalene and chloroform recording the highest frequencies (1.4–3.1%), 2-methylphenol (328 μg/L), 1, 3, 5-trimethylbenzene (59 μg/L) and 2, 4-dimethylphenol (53.4 μg/L) recorded the highest concentrations. Due to differences in lithology and thickness of the vadose zone over different aquifer groups, notable differences in MOs were recorded between aquifer groups. Twenty-one compounds were also detected with the highest concentrations in Granular aquifers; Karst aquifers recorded the lowest concentration and fewest number of compounds. Different land-use types have also resulted in notable differences in MO contamination, particularly for natural land-use types and urban-industrial types. Natural land recorded both the smallest number of compounds and the lowest concentrations; urban and industrial land-use type had 14 compounds not recorded in other land-use types. Principal component analysis results indicated that urbanization and industrialization in the PRD region were the main driving mechanisms of groundwater MO contamination (via discharges of untreated wastewater). This finding was also verified by the strong positive relationships between waste water levels, discharge volume and, chloride concentrations and MO of the shallow groundwater in the PRD.